Radiografi Buick Near Overzicht dengan Sangkaan Cholelithiasis di Rumah Sakit Umum Advent Medan - Sidauruk, Juliana; Sihotang, Sri Nanda (Poltekkes Kemenkes Kendari, 2023)
BNO radiography with suspected cholelithiasis at Medan Adventist Hospital. Scientific writing for Diploma III Radiodiagnostic Engineering and Radiotherapy study program, Sinar Amal Bhakti Foundation, Medan 2021. BNO radiography using X-rays is the right method to display abnormalities in BNO, especially Plain Abdomen with suspected Cholelithiasis. This examination uses the Antero-Posterior Supine projection, and the Antero-Posterior Lateral position. Research carried out at Medan Adventist Hospital Radiology with the type of x-ray aircraft used was the General X-ray Unit with a relatively large capacity in April 2021. The type of research carried out was a qualitative research method, data collection techniques based on observation results. The results of the research obtained from a BNO radiographic examination with suspected cholelithiasis at the Medan Adventist Hospital, namely that an opaque image appeared in the right hypochondrium at the level of L.1. The film processing is carried out using Computer Radiography (CR).